Woman of influence : 9 steps to build your brand, establish your legacy, and thrive - Miller, Jo (Jo Kay) (McGraw-Hill, 2020)
"The proven nine-step strategy for building your brand and taking the reins of business leadership with skill and confidence-tailored just for women. Recent years have seen a rise in women who speak up and take action with a newfound sense of empowerment-and yet many continue to lack clarity about how to stand out as the talented leaders they are. Can you relate? This groundbreaking new guide from Jo Miller-one of today's most sought-after leadership experts-takes you through her clear and proven process to become an effective leader. You'll learn how to identify your leadership strengths, define your unique career niche, shift your mindset from doing to leading, create career-defining moments, step into a leadership role with skill and confidence, and much more. Woman of Influence helps you avoid the 12 most common career pitfalls encountered by women, while also revealing inspiring real-life stories of career transformation, and delivering self-assessments, practical exercises, downloadable worksheets, and checklists that have been road-tested by tens of thousands of professionals. Bridge the gap between where you are and where you want to be by building an unforgettable personal brand, advancing your career without becoming someone you're not, and navigating office politics with the 'street smarts' of a seasoned pro"--